Exercise and cognitive function in people living with HIV: a scoping review. Issue 12 (5th June 2019) - Quigley, Adria; O'Brien, Kelly; Parker, Robin; MacKay-Lyons, Marilyn
Abstract: Background: Since the advent of antiretrovirals, people with HIV are living longer and have improved quality of life. However, 30–60% of these individuals experience cognitive impairment. Fortunately, physical activity has emerged as a management strategy for cognitive impairment. Purpose: To map the evidence on physical activity and cognition in HIV. Methods: We searched five databases using terms related to physical activity and HIV. Two authors independently reviewed titles and abstracts for studies that addressed physical activity/exercise and cognition in people with HIV. Authors reviewed full texts to identify articles that met our inclusion criteria. One author extracted the data, then we collated the results and summarized the characteristics of included studies. Results: Sixteen studies from high-income countries were included; eight were interventional (five randomized controlled trials and three pre-post single group observational studies) and eight were non-interventional studies. The interventional studies included aerobic, resistive, and Tai Chi exercise for 8 weeks to 12 months in duration. Two of eight interventional studies found exercise to benefit self-reported cognition. All eight non-interventional studies showed a positive relationship between physical activity and cognitive function. Conclusions: Results of this study suggest that physical activity may preserve or improve cognition in people living with HIV. Implications for Rehabilitation: Physical activity may play a role in preserving or improving cognition in the human immunodeficiency virus population. Exercise should be prescribed for people with human immunodeficiency virus based on the stage of infection. Rehabilitation professionals should follow current exercise guidelines when prescribing exercise for people living with human immunodeficiency virus.